A CFD study on the Effect of Spacer Orientation on Temperature Polarization in Membrane Distillation Modules - Shakaib, M.; S. M. F., Hasani; Iqbal, Ahmed; R. M., Yunus (Elsevier, 2012)
Computational fluid dynamics (CFD) study in this work examines the effect of spacer orientation, inlet velocity and filament spacing on shear stress distribution and temperature polarization in membrane distillation modules. The CFD simulations show that spacer orientation affects the temperature polarization and heat transfer rates. If spacer filaments touch the top or bottom surfaces of membrane, the temperature polarization is high which results in low heat transfer rates. When these filaments are detached from the membrane, temperature polarization is lower. The shear stress is also found to be higher and local values of temperature polarization index and shear stress are more uniformly distributed in the detached mode making this particular orientation more favorable for use in membrane distillation modules.